A religião em questão: um estudo comparativo sobre a relação entre religião e estado em Brasil e Irã - Wachholz, Rafael de Oliveira (2021)
This work presents a comparative study of the historical trajectories that institutionalized the Brazilian secular democracy and the Iranian theocracy. The research starts from the perception that, quite frequently in the public debate, several representations about the different forms of relationship with religion are sustained. The present text seeks to test these stereotypes on the subject and to identify what are the similarities and diferences between these institutionalities that at first sight seem very different. It is used the technique of path dependence to analyse the historical trajectories of Iran and Brazil that preceded, respectively, the Iranian Revolution and the Constituent Assembly of 1987 and established the Iranian theocratic republic and the Brazilian secular republic. In addition, a documentary analysis of the national constitutions of Iran and Brazil is outlined in order to understand the results of both historical processes within state formality and, in short, to understand similarities and differences between the Iranian theocracy and Brazilian democracy. The research also includes a comparative analysis of both historical processes and their resulted national constitutions. Based on these analyzes, it is possible to outline reflections in the sense that, although an Orientalist narrative sustains a supposed essential difference between the two societies, the processes that make up the relationship between Religion and State are quite dynamic and complex, influenced by contingent elements of history. What defines Brazilian secularism and Iranian theocracy is the relationship between different elements, many of them similar to each other.